HUBUNGAN SIKAP TERHADAP PERAWATAN KESEHATAN GIGI DAN MULUT - Fadlan Tamami; Eppy Setiyowati; Rohmatul Khasanah; Al Silinia Kurnia R; Annisa Rummana M; Sholaikha Khusnul K; Sindy La H (Pusat Riset dan Inovasi Nasional, 2023)
Attitudes in maintaining cleanliness and performing dental and oral care must start from an early age. The causes of dental and oral health problems in the community include behavioral factors or attitudes in ignoring dental and oral care and hygiene. Objective: To analyze the relationship between attitudes in adolescents towards dental and oral health care. Methods: this study uses quantitative research methods and to determine the non-parametric test used in this study is the Chi Square. A sample of 41 youth youth respondents in the Kendangsari data was obtained through a questionnaire. Results. From the results of 41 respondents, 21 respondents (51.2% had a good attitude, 20 respondents (48.8%) had a bad attitude, 24 (58.5%) often performed good dental and oral care, dental care and very bad mouth as many as 17 (41.4%).Conclusion: From the results of this study it can be concluded that dental and oral care at Karang Taruna Kendang Sari Surabaya has no relationship between attitude and dental and oral care.It is hoped that further research and more counseling will be provided. continued on the youth of Karang Taruna Kendang Sari Surabaya.